2019
DOI: 10.3390/ijerph17010284
|View full text |Cite
|
Sign up to set email alerts
|

Projective Technique Testing Approach to the Understanding of Psychological Pain in Suicidal and Non-Suicidal Psychiatric Inpatients

Abstract: Psychological pain is a core clinical factor for understanding suicide, independently from depression. The aim of this study is to assess the role of psychological pain on suicide risk and to evaluate the relationship between psychache and different psychiatric disorders. We conducted the present cross-sectional study on 291 inpatients with a diagnosis of major depressive disorder, bipolar disorder, and schizophrenia. We administered Shneidman's Psychological Pain Assessment Scale (PPAS) for the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…The connection between high levels of psychological pain with the severity of "S" thoughts and acts indicated higher levels of psychological pain in subjects with past and current "S" attempts compared to subjects without attempted suicide (Ducasse et al, 2018). Additionally, significantly higher psychological pain severity was also observed in depressed patients compared to controls (Reist et al, 2017;Berardelli et al, 2020). Shelef (2015) in a group of soldiers of Israel Defence Forces showed that individuals with a low capacity for emotional regulation of psychological pain manifested a higher intensity of psychological pain and had more "S" thoughts.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…The connection between high levels of psychological pain with the severity of "S" thoughts and acts indicated higher levels of psychological pain in subjects with past and current "S" attempts compared to subjects without attempted suicide (Ducasse et al, 2018). Additionally, significantly higher psychological pain severity was also observed in depressed patients compared to controls (Reist et al, 2017;Berardelli et al, 2020). Shelef (2015) in a group of soldiers of Israel Defence Forces showed that individuals with a low capacity for emotional regulation of psychological pain manifested a higher intensity of psychological pain and had more "S" thoughts.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…They found that current psychache and worst-ever psychache were both associated with high suicide risk in their sample. However, no significant differences were found among the three diagnostic groups [49]. The concept of psychache opens new avenues for the investigation of psychopathological symptoms and their relationship to pain.…”
Section: Differences Between Patients Who Experience High Versus Low mentioning
confidence: 85%
“…There is evidence that GABA agents are also effective against pain. Furthermore, the expression of pain depends to a large degree on the relationship of the patient with the person inquiring about the pain [49]. Empowering patients to share in decisions about control of pain has borne positive results [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the TAT as well as the essay requirement may be too demanding for patients with severe psychiatric pathology. Several studies utilized the PPAS in clinical samples ( 40 , 41 , 42 ) and one study in a student sample ( 43 ). Leenaars et al ( 43 )and Pompili ( 42 ) have discussed construct and content validity issues of the PPAS.…”
Section: Measurement Of Psychological Painmentioning
confidence: 99%